Ceramide synthases: insights into the expression and prognosis of lung cancer. (2nd January 2021) - Qian, Huijiang; Deng, Jingjing; Lu, Chao; Hou, Gouxin; Zhang, Hualiang; Zhang, Ming; Fang, Zhixian; Lv, Xiao-Dong
Abstract: CerSs (ceramide synthases), a group of enzymes that catalyze the formation of ceramides from sphingoid base and acyl-CoA substrates. As far, six types of CerSs (CerS1-CerS6) have been found in mammals. Each of these enzymes have unique characteristics, but maybe more noteworthy is the ability of individual CerS isoform to produce a ceramide with a characteristic acyl chain distribution. As key regulators of sphingolipid metabolism, CerSs highlight their unique characteristics and have emerging roles in regulating programmed cell death, cancer and many other aspects of biology. However, the role of CerSs in lung cancer has not been fully elucidated. In this study, there was no significant change in the sequence or copy number of CerSs gene, which could explain the stability of malignant tumor development through COSMIC database. In addition, gene expression in lung cancer was examined using the Oncomine TM database, and the prognostic value of each gene in non-small cell lung cancer (NSCLC) was analyzed by Kaplan-Meier analysis. The results showed that high mRNA expression levels of CerS2, CerS3, CerS4 and CerS5 in all NSCLC patients were associated with improved prognosis. Among them, CerS2 and CerS5 are also highly expressed in adenocarcinoma (Ade), but not in squamous cell carcinoma (SCC). In contrast, high or low expression of CerS1 and CerS6 no difference was observed in patients with NSCLC, Ade and SCC. Integrated the data of this study suggested that these CerSs may be a potential tumor markers or drug target of new research direction.